Deep-Sea Habitats and Megafauna on the Slopes of the São Paulo Ridge, SW Atlantic - Perez, Jose Angel A.; Gavazzoni, Lucas; de Souza, Luis Henrique P.; Sumida, Paulo Y. Gomes; Kitazato, Hiroshi (Frontiers in Marine Science, 2020)
The São Paulo Ridge (SPR) is a 350 km-long linear geological feature located in the Continental Margin off Brazil (Latitude 28 - 29°S, Longitude 40 - 45°W). In 2013, the region was mapped during the SW Atlantic ‘Iata-Piuná’ expedition and explored by a series of deep-sea dives of the manned submersible Shinkai 6500. A digital bathymetric model analyzed for seafloor morphology, delimited four major bathymetric sectors namely plateau, ridge crest, ridge escarpment and ridge foot. These sectors further enclosed 12 morphological features at smaller spatial scales (structural classes) including plains, valleys, peaks, terraces and troughs. Video profiles across the depth gradient (4219 to 2644 m depths) revealed that the slopes of the SPR southern flank were gentle and terraced, mostly covered by biogenic sediments and interrupted by rocky cliffs/crests, dispersed outcrops and loose particles. The North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) overlaid at the escarpment along which they established colder (0.4 - 1.0°C; 4200 – 3400 m) and warmer (2.0-3.0°C; 3400 – 2600 m) habitats, respectively. Physical components were used to define seven seascape units in the ridge foot (2), escarpment (3), and plateau-ridge crest (2), where a total of 914 organisms of the epibenthic and benthopelagic megafauna were recorded. Over 70% of these records were sessile suspension feeders, including sponges (61.5%) and anthozoans (11.4%). Most taxonomic groups concentrated above 3800 m, under the influence of NADW, where densities reached maximum values (mean 0.26 organisms.m-2; 0.024 – 0.027 organisms.m2 95% CI). Also, nearly half of megafauna records concentrated in patches delimited by the 3800 – 3300 m and 2900 – 2700 m isobaths. The deepest patch (3800 - 3300 m) coincided with the interface zone between AABW and NADW, where mixing processes create a density gradient. Evidences suggested that topography-related deep-water flow dynamics, and not substrate availability, drives benthic megafauna distribution at meso-habitat scale.